NEUTRON REFLECTION FROM HEXADECYLTRIMETHYLAMMONIUM BROMIDE ADSORBED AT THE AIR/LIQUID INTERFACE - THE VARIATION OF THE HYDROCARBON CHAIN DISTRIBUTION WITH SURFACE CONCENTRATION - Lu, J; Hromadova, M; Simister, E; Thomas, R; Penfold, J (1994)
We have determined the structure of a monolayer of hexadecyltrimethylammonium bromide adsorbed at the air/water interface at its critical micelle concentration (9.2 × 10-4 M) and at two lower concentrations using neutron specular reflection. We have used isotopic labeling to determine the relative positions of chains, heads, and solvent, and more detailed labeling to determine the distributions of C6 chain fragments at either end of the alkyl chains. The use of the more detailed labeling scheme has allowed us to make a quantitative estimate of the contribution of surface roughness to the structure of the layer at the three concentrations, to show that the alkyl chains are, on average, strongly tilted away from the surface normal but that the part of the alkyl chain next to the head group is less tilted. The different tilt angle distributions for the two ends of the hydrocarbon chain also indicate that there are gauche defects in the chain. © 1994 American Chemical Society.